Base Nacional Comum Curricular: análise crítica de discursos sobre ensino de língua portuguesa - Schmitt, Rosana Maria (2021)
The National Common Curricular Base (BNCC) is a document of normative character, which aims to determine the pedagogical practices developed in the three stages of basic education from a learning set considered essential to Brazilian students. Within the scope of the Portuguese Language curricular component, the document aims to provide experiences that contribute to the expansion of literacies, in order to enable a significant and critical participation of students in the various social practices permeated by language (BRASIL, 2018, p. 67-68). Thus, in view of the importance of investigating this document and proposing a critical reflection in the face of the new pedagogical orientations recommended, we critically analyze the discourses on Portuguese language teaching recurring in the final years of the Elementary school stage of the document. For this, the analysis corpora comprise the pedagogical foundation of the component and the sampling of selected skills from the journalistic-media field and the group of skills aimed at all fields of activity. As a theoretical-methodological contribution, we are anchored in the Critical Discourse Analysis (FAIRCLOUGH, 1989, 2001, 2003), in the Systemic-Functional Grammar (HALLIDAY; MATTHIESSEN, 2004, 2014; FUZER; CABRAL, 2014) and in the theoretical-methodological perspectives for the teaching of Portuguese in Brazil, which we call prescriptive-normative, linguistic-textual, and textual-discursive (SAVIOLI, 2014; SOARES, 2002; ROJO, 2009; TRAVAGLIA, 1996). The results of the analysis point to the existence of a central discourse, aligned with the perspective of textual-discursive teaching, which supports the Portuguese language component in the BNCC Elementary stage. This discourse, recurring in the pedagogical basis and in the skills of the journalistic-media field, has its focus on teaching based on gender(s) and new (multi)literacies, which considers situated and diverse contexts, focuses on the development of practices of uses of idiom and language and reflection on those uses, the critical understanding of texts and discourses that circulate in different spheres of society, the development of reading practices and textual production articulated by the practice of linguistic analysis, and the work with semiotic, cultural and linguistic multiplicity. However, we found that this discourse is fluid and, especially in the skills of the group all fields of activity, it is aligned with a perspective of prescriptive-normative teaching, which is manifested, in general, by discourses centered on the standard norm, which only contemplate the literacies already established in the school context, focus the word and phrase as a unit of analysis or take the text only as a pretext for teaching grammatical rules, without relating it to specific contexts of use. The document production process, in this sense, highlights the tensions identified in the text and reflects the conflicts arising from different perspectives and objectives for Brazilian education involved in this context. Therefore, considering that the discourses expressed by the document echo in the school context and directly influence the teaching practice, we seek to unveil power relations that are behind the document and, thus, contribute to the initial and continuing teachers training, minimizing possible impacts on the implementation process and pedagogical recontextualization of the recommended proposals.